Stylistics: An Analysis of Roald Dahl’s George’s Marvelous Medicine and The Girrafe and The Pelly and Me to Provide Insights on Establishing Writing Style - Simanjuntak S., MAEd, Debora Chaterin (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2016)
This study aims to provide insights on establishing writing style through stylistic analysis on Roald Dahl’s George Marvelous Medicine and The Giraffe and The Pelly and Me. This is a qualitative study which focuses on literary analysis. The data was collected from those two books. Evidently this study will bring benefit to English majors to gain insights on how to establish effective writing style. The findings of this study show that Dahl has four outstanding elements for writing style: Lead Sentences, Rhyme-schemed poem, Peculiar Chosen Words, and Concept of Personification. Although Dahl’s books have great insight on establishing one’s writing style, there are some positive and negative influence that should be considered in reading Dahl’s masterpieces. Keywords: Stylistics, elements of writing style, literary analysis